Opportunity recognition and SME performance: the mediating effect of business model innovation. (19th May 2016) - Guo, Hai; Tang, Jintong; Su, Zhongfeng; Katz, Jerome A.
Abstract : Opportunity recognition is vital for small and medium‐sized enterprises (SMEs), but SMEs face challenges in capturing recognized opportunities. Given that opportunity recognition does not automatically lead to higher SME performance and that SMEs need to take appropriate actions to exploit recognized opportunities to achieve better performance, it is imperative to explore the mediators that enable SMEs to translate opportunity recognition into higher performance. This study proposes that business model innovation may be a key conduit through which opportunity recognition affects SME performance. Based on a dataset of 155 SMEs, we find that the positive relationship between opportunity recognition and SME performance is mediated by business model innovation. These findings not only aid SMEs in accomplishing the performance effect of opportunity recognition, but also provide some insights into the implications of business model innovation.